2012
DOI: 10.18433/j35s3k
|View full text |Cite
|
Sign up to set email alerts
|

α-Amylase Inhibitors: A Review of Raw Material and Isolated Compounds from Plant Source

Abstract: -Inhibition of α-amylase, enzyme that plays a role in digestion of starch and glycogen, is considered a strategy for the treatment of disorders in carbohydrate uptake, such as diabetes and obesity, as well as, dental caries and periodontal diseases. Plants are an important source of chemical constituents with potential for inhibition of α-amylase and can be used as therapeutic or functional food sources. A review about crude extracts and isolated compounds from plant source that have been tested for α-amylase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
324
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 504 publications
(337 citation statements)
references
References 74 publications
10
324
1
2
Order By: Relevance
“…[34] Currently, there are many anti-diabetic drugs that perform mostly for inhibiting carbohydrate digestion and absorption. [14] The pharmaceutical agents are found out as drugs to oppose TIIDM such as Metformin, Sylphonylureas, TZDs, GLP-1 analoges, DDP-4 inhibitors, insulin, Pramlintide, and SGLT-2 inhibitors. [35] These drugs help TIIDM people for maintaining blood glucose level while they still have side effect on the patients likewise.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[34] Currently, there are many anti-diabetic drugs that perform mostly for inhibiting carbohydrate digestion and absorption. [14] The pharmaceutical agents are found out as drugs to oppose TIIDM such as Metformin, Sylphonylureas, TZDs, GLP-1 analoges, DDP-4 inhibitors, insulin, Pramlintide, and SGLT-2 inhibitors. [35] These drugs help TIIDM people for maintaining blood glucose level while they still have side effect on the patients likewise.…”
Section: Discussionmentioning
confidence: 99%
“…[12] Alpha-amylase is also related to the breakdown of long chain carbohydrates and this inhibitor similar to acarbose which defers the digestion of carbohydrate and extends overall the time in the digestion of post-prandial plasma glucose increase. [13,14] Hence alpha-glucosidase and alpha-amylase inhibitors are vital medicines to inhibit the assimilation of carbohydrates in the intestines, can be used to treat TIIDM and impaired glucose tolerance (IGT). [10] In nowadays, many reviewing issues are reported that efficacy medicines are the alternative one of active components for anti-diabetes agents from natural sources or folk herbal medicines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[34] In our work, the main phenolic compounds present in the extract are mono-caffeoyl quinic acid and di-caffeoyl quinic acid which have been previously reported as inhibitors of the key enzymes of carbohydrates digestion process. [35] However, it was also considered that minor components, as well as a possible interaction between the substances could also affect the biological activities. Several reports have shown close relationship between total phenolic contents and antioxidative activity of plant extracts.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…A wide array of numerous chemical compounds has demonstrated activity consistent with their possible use in the treatment of diabetes [9][10][11][12]. Different plants have been reported to show α-amylase inhibitory activity and so may be relevant to the treatment of diabetes [13,14]. The potential role of the medicinal plants as inhibitors…”
Section: Introduction mentioning
confidence: 99%